The clinical atlas of cardiomyopathies: data from the prospective DZHK TORCH study. (25th November 2020) - Sedaghat-Hamedani, F; Trebing, J; Kindermann, A; Kayvanpour, E; Tan, K; Preussler, S; Sluka, S; Gi, W.T; Dieterich, C; Weitmann, K; Eschenhagen, T; Hoffmann, W; et al.
Abstract: Introduction: Cardiomyopathies (CMPs) are leading causes of heart failure (HF) and sudden cardiac death (SCD). Comparative data of the multiple cardiomyopathy forms are largely missing. The TranslatiOnal Registry for CardiomyopatHies (TORCH) is the largest prospective multicentre CMP registry world-wide. Enrolled patients are comprehensively phenotyped by clinical examinations, state-of-the-art imaging, and molecular investigations. In this study, we present the baseline and 1-year follow-up data. Methods: TORCH is a national, prospective, multicentre registry within the German Centre for Cardiovascular Research (DZHK) and includes 2300 patients with non-ischemic (primary and secondary) CMP from 20 centres. The minimum follow up was one year. The DZHK-wide harmonization of datasets and SOPs ensure a high level of data quality and comparability across different CMP forms. Results: Dilated cardiomyopathy (DCM) has the highest prevalence with 64% of all enrolled patients, followed by hypertrophic cardiomyopathy (HCM) with 16%. At baseline, patients with arrhythmogenic right ventricular cardiomyopathy (ARVC) were treated more often with ICD implantation and showed high rates of adequate ICD therapies (65.8%, p<0.05 and 47.8%, p<0.05, respectively). The prevalence of stroke or transient ischemic attack (TIA) was in multivariate analysis significantly higher (p<0.05) in left ventricular non-compaction cardiomyopathy (LVNC, 14.9%), while atrial fibrillation was lower than in other cardiomyopathy forms. Patients with amyloidosis had the worst outcome (HR: 6; 95% CI: 2.5–14.5, P<0.05) with annual mortality of >15% and 12% receiving heart transplantation. In DCM, reverse remodelling with improvement of functional parameters and biomarkers was more often observed in idiopathic and inflammatory cases compared to familial ones. HCM patients had the most favourable outcome. Conclusion and outlook: TORCH is the largest prospective study focusing on CMPs. We provided for the first time prospectively the clinical data of patients with diverse cardiomyopathies with outcome. Furthermore, comparing the different CMP forms on the clinical and molecular level will be an important step to enable translational research projects. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): German Centre for Cardiovascular Research (DZHK)